Implications Of The Omnibus Law On The Dual Role: Social Risks For Women In The Balinese Tourism Industry - Budi Shantika; Astuti Wijayanti (Utan Kayu Publishing, 2025)
This research aims to identify the impact of the implementation of the Omnibus Law (UU Cipta Kerja) on the position of women in the tourism sector in Bali, focusing on the social and cultural risks faced by female workers due to changes in labor policies. This study explores the role conflicts between traditional duties and job demands arising from labor deregulation. Using a qualitative methodology approach, data were collected through a literature review, document analysis of legal texts, academic articles, government reports, and news articles. The data were then analyzed using content analysis to identify key themes, such as the dual burden faced by women, social tensions, and the impact of policy changes on the well-being of female workers in Bali's tourism sector. The findings reveal that the implementation of the Omnibus Law worsens the social and economic conditions of female workers in the tourism sector by removing key labor protections such as menstrual leave and maternity leave. Challenges, such as the lack of gender-sensitive policies and cultural considerations continue to hinder the full potential of these workers. The study concludes that the Omnibus Law negatively impacts women's well-being, highlighting the need for labor policy reforms that are more inclusive of gender and culture to reduce inequalities and better support Balinese women in balancing their professional and traditional roles. Recommendations for future policy changes include implementing protections for female workers, ensuring cultural sensitivity, and providing better support systems for women in the workforce.